Stress resistance as a professionally significant trait of the future rehabilitators in the system of physical education - Otravenko, Olena; Shkola, Olena; Zhamardiy, Valeriy; Dubovoi, Oleksandr; Cherednychenko, Inna; Halashko, Valeriia; Lopuga, Anna (My University, 2025)
The aim of the study is to determine the level of stress resistance of the future rehabilitators in the system of physical education as a professionally significant feature and the impact of stress resistance on the preservation of mental health of participants in the educational process. Materials and Methods: The study was conducted during 2022–2024, in which 320 respondents from following institutions took part: Luhansk Taras Shevchenko National University, Municipal Establishment «Kharkiv Humanitarian Pedagogical Academy» of Kharkiv, Regional Council, Poltava State Medical University, National University «Zaporizhzhia Polytechnic». Results: The results of the study contributed to the development of research skills through the method of analysis and improvement of students’ practical skills. They were involved in research work (writing qualification papers on the topic of research, writing articles and theses, participation in scientific and professional quests, conferences of various levels, including international ones; participation in trainings, master classes, development of mini-projects on health care activities). 12 discussions on the topic of research, 6 trainings, 6 guest lectures, 3 scientific and professional quests were held, the content of 10 educational programs was updated, students were trained in partner institutions under the internal mobility program. Conclusions: The use of psychocorrective programs in working with young people to develop stress resistance and improve mental health allows to significantly improve their psychological state, adaptation and socialization.
Keywords: фізична активність; стресостійкість; фізичне виховання; фізична реабілітація; психічне здоров'я; майбутні бакалаври; physical activity; stress resistance; physical education; physical rehabilitation; mental health; future bachelors